PENGARUH PEMBERIAN PUPUK EKSKRESI CACING TANAH (KASCING) TERHADAP KELIMPAHAN Nannochloropsis sp. SEBAGAI PAKAN ALAMI IKAN BUDIDAYA - Rina Marito Daulay; Pindi Patana; Indra Lesmana (AQUACOASTMARINE, 2014)
The current of aquaculture development is not accompanied with sufficient fry supply due to some constraints and difficulties in the supply of life food. The life food culture Nannochloropsis sp. by using vermicompost fertilizer has never been used before, while the vermicompost contains nutrient required by cells of Nannochloropsis sp. to support the growth and reproductions. The purpose of this research is to know the influence of the vermicompost fertilizer treatments on the abundance of the cells Nannochloropsis sp. and how much the optimum concentration. This research was conducted in Balai Budidaya Air Payau (BBAP) Ujung Batee, Banda Aceh. The threatment of life food culture was done with 10 liters volume of water about 10 days. Parameter were observed are the growth of abundance Nannochloropsis sp. cells and quality of water. The used by completely randomized design with 5 treatments and 3 times repeatitions. Those 5 treatments are as follows the control treatment with technical fertilizer, 0 ppm (without treatment vermicompost), 50 ppm, 100 ppm, and 150 ppm. The treatments vermicompost fertilizer is effect on the abundance Nannochloropsis sp., the optimum concentration 100 ppm and the medium abundance in day 5 with density 6.895.000 cells/ml.Keywords : Nannochloropsis sp., vermikompost, abundance